Hadith #2343 - Sunan Abi Dawud - al-Harith bin Ziyad الحارث بن زياد; Amr bin Muhammad bin Bukayr; Arbad bin Sariyya al-Salmi; Hmad bin Khalid al-Khyat حماد بن خالد الخياط القرشي; Mu'awiya bin Salah bin Hadayr معاوية بن صالح بن حدير; Yonus bin Syf يونس بن سيف (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: The difference between our fasting and that of the people of the Book is eating shortly before dawn.
Grade: Sahih

Hadith #3049 - Sunan Abi Dawud - Arbad bin Sariyya al-Salmi; Artah bin al-Mundhir bin al-Aswad أرطاة بن المنذر بن الأسود; Hkym bin 'Umayr bin al-Ahws حكيم بن عمير بن الأحوص; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان (Sunan Abi Dawud)
Harb ibn Ubaydullah ibn Umayr ath-Thaqafi told on the authority of his grandfather, a man of Banu Taghlib: I came to the Prophet (ﷺ), embraced Islam, and he taught me Islam. He also taught me how I should take sadaqah from my people who had become Muslim. I then returned to him and said: Messenger of Allah, I remembered whatever you taught me except the sadaqah. Should I levy tithe on them? He replied: No, tithes are to be levied on Christians and Jews.
Grade: Da'if